Association of an Index of Healthy Aging With Incident Cardiovascular Disease and Mortality in a Community-Based Sample of Older Adults. (26th April 2016) - McCabe, Elizabeth L.; Larson, Martin G.; Lunetta, Kathryn L.; Newman, Anne B.; Cheng, Susan; Murabito, Joanne M.
Abstract: Background: The healthy aging index (HAI) was developed as a marker of health in multiple systems that can identify individuals who age most successfully. Methods: We calculated an HAI in 934 Framingham Offspring Study participants aged 60 or older at baseline. Heart rate and C-reactive protein (CRP) were added in modified versions of the HAI. Cox proportional hazard models were used to quantify the association of the HAI with mortality, cardiovascular disease (CVD), and cancer. We used fully conditional specification to multiply impute missing values for HAI components, increasing the sample size by 44%. Results: Over 10 years of follow-up, there were 138 deaths, 103 incident cases of CVD, and 138 incident cases of cancer. In models adjusted for age, sex, and behavioral risk factors, the HAI was associated with mortality (hazard ratio [HR] per unit of HAI 1.24, 95% confidence interval [CI] 1.13–1.36) and with CVD (HR 1.27, 95% CI 1.13–1.42), but not with cancer (HR 1.01, 95% CI 0.91–1.11) in observed (non-missing) data. In multivariable models further adjusting for prevalent diseases, results were slightly attenuated. When including heart rate and CRP, a modified HAI gave stronger associations. Results with imputed data are similar to results from complete case analyses. Conclusions: In our large community-based sample, the HAI is a strong predictor of mortality and CVD. Other factors that are strongly associated with mortality, such as heart rate and CRP can improve the ability of the HAI to identify the healthiest older adults.